2020
DOI: 10.1186/s12877-020-01574-z
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal association between housing accessibility and activities of daily living: the role of self-efficacy and control in people ageing with Parkinson’s disease

Abstract: Background: External housing-related control beliefs (HCB) and general self-efficacy (GSE) influence different health outcomes in the general ageing population, but there is no information of their role in people ageing with Parkinson's disease (PD). This study aimed to longitudinally assess the role of external HCB and GSE on the association between housing accessibility and activities of daily living (ADL) among people ageing with PD. Methods: Baseline and 3-year follow-up data on 130 community-living partic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Most HA clients receive health and social care in parallel, e.g., provision of mobility devices and assistance with activities of daily living (ADL) [ 12 , 13 , 14 ]. Previous research has shown that HA has a positive effect on activity, such as reduced dependence in ADL and increased activity performance [ 8 , 15 , 16 ], usability in the home [ 8 ], improved fall-related outcomes [ 17 , 18 ], and self-rated health [ 19 , 20 ]. Hence, it seems that a HA can counteract disability.…”
Section: Introductionmentioning
confidence: 99%
“…Most HA clients receive health and social care in parallel, e.g., provision of mobility devices and assistance with activities of daily living (ADL) [ 12 , 13 , 14 ]. Previous research has shown that HA has a positive effect on activity, such as reduced dependence in ADL and increased activity performance [ 8 , 15 , 16 ], usability in the home [ 8 ], improved fall-related outcomes [ 17 , 18 ], and self-rated health [ 19 , 20 ]. Hence, it seems that a HA can counteract disability.…”
Section: Introductionmentioning
confidence: 99%
“…Feeling competent about the set of experiences they may develop in the home increases affective, cognitive, and social aspects. Feeling competent and having control over the home is important since in the aging process, older people make the home the place of participation and social relations and they give it greater significance [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Shih et al 34 had one section focusing on whether PD treatments were related to the risk of nursing home admission. In addition to a study protocol 24 including one psychometric study28 the aims of the empirical studies from Sweden 23,[25][26][27]29 concerned different aspects of housing, framed in the context of environmental gerontology, and related to general as well as PD-specific aspects of health. The methodological study from Thailand 31 included the development and piloting of a home assessment questionnaire, while the study from the United Kingdom 33 aimed to investigate in-home sensors for data collection about fall risks.…”
Section: Publication and Study Characteristicsmentioning
confidence: 99%